Analysis of photovoltaic hosting capacity calculation in electrical distribution networks - Coleto Lázaro, Juan Isidro; Velásquez Mallqui, William; Villavicencio Gastelu, Joel; Obispo Vásquez, Angel Eduardo (LACCEI, 2024)
In recent years, a steady growth in the number of photovoltaic systems (SFV) in homes has been observed. The uncontrolled integration of these systems brings operational problems in the electrical distribution network, such as overvoltage. Therefore, it is important to determine the maximum amount of photovoltaic generation that can be connected to a distribution network without experiencing operational problems (hosting capacity). In this work, it is evaluated how different considerations in the development of photovoltaic integration influence the value of hosting capacity. For this purpose, three different distributions of the location of the SFVs are analyzed: (1) the SFVs are preferentially in nodes close to the source, (2) the SFVs are randomly distributed and (3) the SFVs are preferentially in the far nodes. to the source. The results showed that the voltage increases in case (1) are lower than those obtained in cases (2) and (3). The largest increases in tension were observed in case (3). For example, it was found that for a PV penetration level of 50%, the voltage increases were 49%, 58% and 69%, respectively. Concerning the hosting capacity, photovoltaic penetration values of 66.66%, 58.33% and 50% were obtained in cases (1), (2) and (3), respectively. Therefore, it was evident how the value of hosting capacity is influenced by the development of photovoltaic integration.